ANALISIS MENGENAI UU PEMILU NOMOR 7 TAHUN 2017 DENGAN MODEL MERILEE S. GRINDLE (Jurnal Nawala Politika, 2023)
Election Regulations was passed by the President on August 15 2017, this regulation contain various policies regarding the terms and conditions for holding elections. To Grindle Implementation of the policy is a general process of administrative action that can be examined at several program levels. Meanwhile, Van Meter and Horn argue that policy implementation is an action taken by the government and the private sector, both individually and collectively, to achieve a certain goal. Policy implementation does not always run smoothly, there are always pros and cons that come with it. Policies that are sufficient to generate polemics, one of which is the presidential threshold. Thus altering policy goal by having conflict of interest. Keywords: Constitution; Election; Policy;